Uneven Experiences: The Impact of Student-Faculty Interactions on International Students’ Sense of Belonging - Glass, Chris R.; Kociolek, Elizabeth; Wongtrirat, Rachawan; Lynch, R. Jason; Cong, Summer (Journal of International Students, 2015)
This study examines student-faculty interactions in which U.S. professors signal social inclusion or exclusion, facilitating–or inhibiting–international students’ academic goal pursuits. It compares narratives of 40 international students from four purposefully sampled subgroups – academic preparedness (low, high) and financial resources (low, high). Overall, international students’ interactions with professors were marked by joy, trust, anticipation, and surprise. Nonetheless, the narratives exhibit two significant sources of variation: narratives from the low financial resources, high academic preparedness subgroup reflected widely-varied experiences interacting with professors, and narratives from the low financial, low academic preparedness subgroup lacked any descriptions of positive student-faculty interactions.